Sequence Analysis of Rifampicin Resistance Determining Region (RRDR) of Mycobacterium tuberculosis - Shrestha, Mitesh; Chaudhary, Hemanta Kumari; Chaudhary, Pradip Kumar; Poudel, Bal Hari (Journal of Tropical Life Science, 2018)
Mycobacterium tuberculosis has become the cause for one of the most dreadful disease which the mankind has ever known i.e. Tuberculosis. The organism holds the ability to infect multiple organs at a time resulting in multiple symptomatic presentations in pathogenic condition while in non-pathogenic condition, it can lay dormant and remain asymptomatic. The research work presented here aimed at sequencing of Rifampicin Resistance Determining Region (RRDR) of the rpoB gene present in phenotypically multidrug resistant M. tuberculosis. The findings showed that the major point of mutations to be present within this region was at codon 516, 526, and 531. Early diagnosis of multidrug resistance in any pathogen has become a pre – requisite for proper treatment and efficient elimination of pathogenic organisms from the host with minimal toxicity. Similarly, understanding the mutation dynamics of target genes also help in novel drug design and discovery.